Implementation of FRISTA Biometric Technology in Orthopedic Outpatient Registration Services at X Regional General Hospital - Labiqa, Nazwa Adzraa; Khasanah, Lina; Karmanto, Bambang; Mohammad, Maula Ismail (LPPM Universitas Dhyana Pura, 2026)
The implementation of biometric technology in healthcare services is one of the digital innovations aimed at improving efficiency, accuracy, and the quality of patient services. One of its applications is the FRISTA system, which is based on face recognition technology and used in the outpatient registration process at the Orthopedic Clinic of X Regional General Hospital. This study aims to evaluate the level of user satisfaction with the FRISTA system using the End User Computing Satisfaction (EUCS) method. This study employed a quantitative descriptive approach with a population of 1,964 patients who used the FRISTA system during the period of July to September 2025. The research sample consisted of 95 respondents, determined using the Slovin formula. Data were collected through a five-point Likert scale questionnaire covering the five dimensions of EUCS, namely content, format, accuracy, timeliness, and ease of use. The data were analyzed descriptively using Microsoft Excel. The results showed that all dimensions were categorized as satisfactory, with content scoring 4.14, format 4.09, accuracy 4.03, timeliness 4.13, and ease of use 4.12. The highest score was obtained in the content dimension, while the lowest was found in the accuracy dimension, particularly in aspects related to technical disruptions or system errors. Overall, the FRISTA system was considered capable of supporting the outpatient registration process in an informative, efficient, and user-friendly manner. However, improvements in technical stability, real-time data updates, and feature development are still needed to further enhance service quality and optimize user satisfaction.